2020
DOI: 10.1371/journal.pone.0228015
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis in pancreatic cancer promotes cancer cell migration and invasion by release of CXCL5

Abstract: BackgroundNecroptosis is a form of programmed cell death that is accompanied by release of intracellular contents, and reportedly contributes to various diseases. Here, we investigate the significance of necroptosis in pancreatic cancer. MethodsWe used immunohistochemistry and western blot analysis to evaluate expression of the key mediators of necroptosis-receptor-interacting serine/threonine protein kinase 3 (RIP3) and mixed lineage kinase domain-like (MLKL)-in human pancreatic cancer. We also tested the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 55 publications
1
59
0
Order By: Relevance
“…CENPF, for instance, has been related to worse outcomes and survival in several cancer types ( 80 , 81 ). Another outstanding example is the MLKL gene, which was shown to be up-regulated in pancreatic cancer, as we observed with Reboot, especially in tumor-invasion conditions ( 82 ). The transcription factor TFDP1 is a gene with significant somatic copy number alterations and corresponding somatic gene expression changes were observed in papillary thyroid carcinomas ( 83 ), even though whose functions remain uncovered in cancer.…”
Section: Discussionsupporting
confidence: 54%
“…CENPF, for instance, has been related to worse outcomes and survival in several cancer types ( 80 , 81 ). Another outstanding example is the MLKL gene, which was shown to be up-regulated in pancreatic cancer, as we observed with Reboot, especially in tumor-invasion conditions ( 82 ). The transcription factor TFDP1 is a gene with significant somatic copy number alterations and corresponding somatic gene expression changes were observed in papillary thyroid carcinomas ( 83 ), even though whose functions remain uncovered in cancer.…”
Section: Discussionsupporting
confidence: 54%
“…For example, elevated levels of CXCL5 were detected in human NSCLC that was related to the vascularity of these tumors [12]. Ando et al research showed that CXCL5 could promote pancreatic cell migration and invasion by mediating the necroptosis [13]. Recently, Liu et al reported that overexpression of CXCL5 dramatically attenuated the suppressive effects of cell proliferation, migration and invasion induced by ROR-α-1 overexpression in hepatocellular carcinoma [14].…”
mentioning
confidence: 99%
“…Tumors of PDAC patients with higher CXCL5 expression had more intratumoral M2 polarized macrophages, neutrophils, and IgG + plasma cells than patients with lower CXCL5 expression (14). At the same time, necroptotic cells also released CXCL5 to promote cancer cell migration and (15). The combined effect of CXCL5 and the receptor CXCR2-ligand helped establish an immunosuppressive microenvironment in PDAC, which has been reported to be associated with unfavorable survival of PDAC patients (7,16).…”
Section: Discussionmentioning
confidence: 96%